Konsep Khilafah Menurut Sayyid Quthb dan Taqiyuddin Al-Nabhani dalam Perspektif Syiasyah Syar’iyyah - Nurhadi Nurhadi; Mawardi Dalimunthe (LP2M STIT Palapa Nusantara, 2020)
The purpose of this study is to find out the concept of khilafah according to Sayyid Quthub and Taqiyuddin al-Nabhani, differences and legal basis. This study is a library model, with primary data sources, the Zhilalal-Qur'anic Tafseer and Nizham Al-Hukmi Fi Al-Islam and qualitative descriptive analysis methods. The result is the thought of the concept of khilafah according to sayyid Quthub: 1). The concept of the ruler / caliph, that who becomes the ruler of the choice of the Muslims, acts in absolute freedom, but that person gets the authority because he constantly applies the law of Allah Almighty. 2). The Islamic government system, the Supra Nasional government (the unity of the entire Islamic world). 3). The pillars of his Islamic government: a). Justice of the ruler; b). People's obedience; c). Consultation between the people and the authorities. Thought of the concept of the Caliphate according to Taqiyuddin Al-Nabhani: 1). The concept of the ruler / caliph is a person who represents the Ummah in government affairs and power and in applying syara 'laws. 2). The system of government is khilafah. 3). The pillars of his Islamic government: a). Sovereignty in the hands of syara '; b). Power of the people; c). To appoint a legal Caliph fardlu for all Muslims; d). Only Khailfah has the right to carry out tabanni (adoption) against syara 'laws; e) The Caliph has the right to make constitutions and all other laws. The differences in the concept of khilafah are both: 1). According to Sayyid Quthub, if the ruler fails, then the ruler can be dismissed if the Muslims are no longer satisfied with him. This statement gives a signal that the people get rid of the rulers who no longer fulfill their functions (zhalim rulers). It is different from the opinion of Taqiyuddin al-Nabhani. An Amir al-mu'minin (Khalifah), even though he is responsible before the people and his representatives, but the people and their representatives are not entitled to dismiss him. Nor will the Caliph be dismissed, except when deviating from Shara law. The one who determined the dismissal was only the Mazhalim court. 2). The system of Islamic government according to Sayyid Quthub does not question any system of government in accordance with the system of conditions of society, but this government is characterized by respect for the supremacy of Islamic law (shari'ah). Whereas According to Taqiyuddin Al-Nabhani that the system of Islamic government is khilafah. 3). The pillars of Islamic government according to Sayyid Quthub and Taqiyyuddin al-Nabhani, points three parts a and b at the above conclusions are: 1). Sayyid Quthub: a). Justice of the ruler; b). People's obedience; c). Consultation between the people and the authorities. 2). Taqiyyuddin al-Nabhani: a). Sovereignty in the hands of syara; b). Power of the people; c). To appoint a legal Caliph fardlu for all Muslims; d). Only Khailfah has the right to do tabanni (adoption) against the laws of shara; e). The Caliph has the right to make constitutions and all other laws. The legal bases for determining the Caliphate according to both: 1). The legal basis for the establishment of the Caliphate according to Sayyid Quthub: 1). Ruler, Qur'an Surah (2) al-Baqarah verse 30; 2). Islamic Government System, Qur'an Surah (24) an-Nur verse 55; 3). Pillars of Islamic Government, Qur'an Surah (4) an-Nisa 'verse 58. 2). The legal basis for the establishment of the Caliphate according to Taqiyyuddin al-Nabhani: 1). Ruler, hadith of Muslim history from Abu Said Al khudri, Hadith no. 1853 and Muslims from Abdullah Bin Amru Bin Ash, Hadith no. 1844; 2). Islamic Government System, Al-Qur'an surah an-Nisa '(4) verse 59, an-Nisa' (4) verse 65. Muslim, saheeh Muslim, volumes, 3 pp., 1459 and 1480; 3). Islamic Pillars of Government al-Qur'an surah An-Nisa (3) verse 65, and Surah An-Nisa (3) verses': 5.